The Preparation of Soluble Cellouronic Acid Sodium Salt by 4-Acetamide-TEMPO Mediated Oxidation of Ultrasound-Pretreated Parenchyma Cellulose from Bagasse Pith - GAO, Xin; CHEN, Keli; ZHANG, Heng; PENG, Lincai (Archives of Acoustics, 2014)
The parenchyma cellulose isolated from bagasse pith was used as an alternative resource for preparation of water-soluble cellouronic acid sodium salt (CAS). The influence of ultrasound treatment on the cellulose was investigated for obtaining CAS by regioselective oxidization using 4-acetamide-TEMPO and NaClO with NaClO_2 as a primary oxidant in an aqueous buffer at pH 6.0. The yield, carboxylate content and polymerization degree (DP) of CAS were measured as a function of ultrasonic power, agitating time and cellulose consistency by an orthogonal test. The ultrasound-treated conditions were further improved by discussion of ultrasonic power, the most important factor influencing the yield and DP. An optimized CAS yield of 72.9% with DP value (DPv) of 212 was found when the ultrasonic strength is 550 W, agitating time is 3 h and cellulose consistency is 2.0%. The oxidation reactivity of cellulose was improved by ultrasonic irradiation, whereas no significant changes in crystallinity of cellulose were measured after ultrasonic treatment. Moreover, the ultrasound treatment has a greater effect on yielding CAS from parenchyma cellulose than from bagasse fibrous’ one. The CAS was further characterized by Fourier transform infrared spectroscopy (FT-IR) and Scanning electron microscopy (SEM).